A Signature of N6-methyladenosine Regulator-Related Genes Predicts Prognoses and Immune Responses for Head and Neck Squamous Cell Carcinoma - Chen, Junjun; Lu, Tianzhu; Zhong, Fangyan; Lv, Qiaoli; Fang, Min; Tu, Ziwei; Ji, Yulong; Li, Jingao; Gong, Xiaochang (Frontiers in Immunology, 2022)
This study aimed to construct a signature of N6-methyladenosine (m6A) regulator-related genes that could be used for the prognosis of head and neck squamous cell carcinoma (HNSCC), and to clarify the molecular and immune characteristics and benefits of immune checkpoint inhibitor (ICI) therapy using the prognostic signature to define the subgroups of HNSCC. Eighteen m6A regulators were abnormally expressed in the Cancer Genome Atlas (TCGA) HNSCC tissues, compared to those in normal tissues. In total, 1598 m6A regulator-related genes were identified through conducting correlation analysis between m6A regulators and gene expression levels, methylation, and copy number variations in HNSCC patients. A signature of 12 m6A regulator-related genes was constructed using the Cox risk model, combined with the least absolute shrinkage and selection operator (Lasso) variable screening algorithm. According to the median of the signature risk score, the patients were divided into high- and low-risk groups. The Kaplan–Meier survival curve showed that patients with high-risk scores demonstrated poorer overall survival (OS) than those with low-risk scores based on TCGA-HNSCC data (p <0.001). The OS of high-risk patients was significantly worse than that of low-risk patients in the GSE65858 (p <0.001) and International Cancer Genome Consortium (ICGC) oral cancer cohorts (p =0.0089). Immune infiltration analyses showed that 8 types of immune cell infiltration showed highly significant differences between the two risk groups (p <0.001). In the Imvigor210CoreBiologies dataset, the objective response rate (ORR) of the low-risk group (32%) was significantly higher than that of the high-risk group (13%). Additionally, patients in the high-risk group presented with a more significantly adverse OS than that of the low-risk group (p =0.00032). GSE78220 also showed the ORR of the low-risk group (64%) was higher than that of the high-risk group (43%) and the OS of low-risk patients was better than that of high-risk patients (p =0.0064). The constructed prognostic signature, based on m6A regulator-related genes, could be used to effectively distinguish between prognoses for HNSCC patients. The prognostic signature was found to be related to the immune cell infiltration of HNSCC; it might help predict the responses and prognoses of ICIs during treatment.